In‐depth proteomic analysis reveals unique subtype‐specific signatures in human small‐cell lung cancer. Issue 9 (23rd September 2022) - Szeitz, Beáta; Megyesfalvi, Zsolt; Woldmar, Nicole; Valkó, Zsuzsanna; Schwendenwein, Anna; Bárány, Nándor; Paku, Sándor; László, Viktória; Kiss, Helga; Bugyik, Edina; Lang, Christian; Szász, Attila Marcell; et al.
Abstract: Background: Small‐cell lung cancer (SCLC) molecular subtypes have been primarily characterized based on the expression pattern of the following key transcription regulators: ASCL1 (SCLC‐A), NEUROD1 (SCLC‐N), POU2F3 (SCLC‐P) and YAP1 (SCLC‐Y). Here, we investigated the proteomic landscape of these molecular subsets with the aim to identify novel subtype‐specific proteins of diagnostic and therapeutic relevance. Methods: Pellets and cell media of 26 human SCLC cell lines were subjected to label‐free shotgun proteomics for large‐scale protein identification and quantitation, followed by in‐depth bioinformatic analyses. Proteomic data were correlated with the cell lines' phenotypic characteristics and with public transcriptomic data of SCLC cell lines and tissues. Results: Our quantitative proteomic data highlighted that four molecular subtypes are clearly distinguishable at the protein level. The cell lines exhibited diverse neuroendocrine and epithelial–mesenchymal characteristics that varied by subtype. A total of 367 proteins were identified in the cell pellet and 34 in the culture media that showed significant up‐ or downregulation in one subtype, including known druggable proteins and potential blood‐based markers. Pathway enrichment analysis and parallel investigation of transcriptomics from SCLC cell lines outlined unique signatures for each subtype, such as upregulated oxidative phosphorylation in SCLC‐A, DNA replication in SCLC‐N, neurotrophin signalling in SCLC‐P and epithelial–mesenchymal transition in SCLC‐Y. Importantly, we identified the YAP1 ‐driven subtype as the most distinct SCLC subgroup. Using sparse partial least squares discriminant analysis, we identified proteins that clearly distinguish four SCLC subtypes based on their expression pattern, including potential diagnostic markers for SCLC‐Y (e.g. GPX8, PKD2 and UFO). Conclusions: We report for the first time, the protein expression differences among SCLC subtypes. By shedding light on potential subtype‐specific therapeutic vulnerabilities and diagnostic biomarkers, our results may contribute to a better understanding of SCLC biology and the development of novel therapies. Abstract : The first mass spectrometry–based proteomic analysis on small‐cell lung cancer (SCLC) cell lines, reporting unique proteomic profiles of its proposed molecular subtypes. SCLC subgroups detected by proteomics are consistent with mRNA‐based subtypes. Unique proteomic profiles of SCLC subtypes highlight potential subtype‐specific therapeutic vulnerabilities and diagnostic biomarkers.